Age-related increases in long-range connectivity in fetal functional neural connectivity networks in utero. (February 2015) - Thomason, Moriah E.; Grove, Lauren E.; Lozon, Tim A.; Vila, Angela M.; Ye, Yongquan; Nye, Matthew J.; Manning, Janessa H.; Pappas, Athina; Hernandez-Andrade, Edgar; Yeo, Lami; Mody, Swati; Berman, Susan; et al.
Highlights: We examined patterns of connectivity in human fetal brain networks. The fetal brain demonstrates cerebral-cerebellar and cortical-subcortical connectivity. Many forms of cerebral connectivity are present by the third trimester. Default mode network connections were evident in fetuses older than 35 weeks. Long-range functional connectivity is more prominent in older fetuses. Abstract: Formation of operational neural networks is one of the most significant accomplishments of human fetal brain growth. Recent advances in functional magnetic resonance imaging (fMRI) have made it possible to obtain information about brain function during fetal development. Specifically, resting-state fMRI and novel signal covariation approaches have opened up a new avenue for non-invasive assessment of neural functional connectivity (FC) before birth. Early studies in this area have unearthed new insights about principles of prenatal brain function. However, very little is known about the emergence and maturation of neural networks during fetal life. Here, we obtained cross-sectional rs-fMRI data from 39 fetuses between 24 and 38 weeks postconceptual age to examine patterns of connectivity across ten neural FC networks. We identified primitive forms of motor, visual, default mode, thalamic, and temporal networks in the human fetal brain. We discovered the first evidence of increased long-range, cerebral-cerebellar, cortical-subcortical, and intra-hemispheric FC with advancing fetal age. Continued aggregation of data about fundamental neural connectivity systems in utero is essential to establishing principles of connectomics at the beginning of human life. Normative data provides a vital context against which to compare instances of abnormal neurobiological development.